2022
DOI: 10.1007/s00294-022-01248-w
|View full text |Cite
|
Sign up to set email alerts
|

Nab3 nuclear granule accumulation is driven by respiratory capacity

Abstract: Numerous biological processes involve proteins capable of transiently assembling into subcellular compartments necessary for cellular functions. One process is the RNA polymerase II transcription cycle which involves initiation, elongation, co-transcriptional modification of nascent RNA, and termination. The essential yeast transcription termination factor Nab3 is required for termination of small non-coding RNAs and accumulates into a compact nuclear granule upon glucose removal. Nab3 nuclear granule accumula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…mitochondrial defects (Hutchinson et al, 2022). In this light the significant upregulation of mitochondrial respiratory associated genes observed here indicates a similar mitochondrial involvement of Sky1 in C. albicans.…”
Section: Pathway Analyses Indicate Conserved Functions For Sky1 Where...supporting
confidence: 77%
See 1 more Smart Citation
“…mitochondrial defects (Hutchinson et al, 2022). In this light the significant upregulation of mitochondrial respiratory associated genes observed here indicates a similar mitochondrial involvement of Sky1 in C. albicans.…”
Section: Pathway Analyses Indicate Conserved Functions For Sky1 Where...supporting
confidence: 77%
“…These processes are consistent with reported functions of Sky1 in S. cerevisiae where this kinase has been described to regulate various steps in RNA maturation and transport ( Gilbert et al., 2001 ). In addition, a recent study has shown that the deletion of Sky1 in S. cerevisiae leads to mitochondrial defects ( Hutchinson et al., 2022 ). In this light the significant upregulation of mitochondrial respiratory associated genes observed here indicates a similar mitochondrial involvement of Sky1 in C. albicans .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the importance of Nab3 nuclear granules [ 95 ] deserves further investigations (also for Nrd1 PrLD) and anticipates new roles of NNS in the regulation of the stress response.…”
Section: Discussionmentioning
confidence: 99%